1999
DOI: 10.1038/sj.jp.7200049
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Chylothorax in Neonatal Thyrotoxicosis

Abstract: We report a patient with congenital chylothorax who also had neonatal thyrotoxicosis secondary to maternal Graves' disease. Fetal tachycardia with hydrops was detected at 28 weeks' gestational age. The fetus responded to antithyroid medication in utero but had persistent bilateral pleural effusion. At birth, he had respiratory distress due to massive pleural effusion. Cytologic studies of pleural fluid were consistent with chylothorax. To the best of our knowledge, the association of congenital chylothorax wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…Previously, it has been suggested that pleural effusions with a lymphocyte count above 80% confer a better outcome and support the diagnosis of primary fetal hydrothorax . By definition, primary fetal hydrothorax is a diagnosis of exclusion once causes for secondary hydrothorax are ruled out (eg, genetic conditions, immune hydrops, thoracic masses, and infection) and preliminary evaluation of fetal hydrothorax include the ruling out such potential causes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been suggested that pleural effusions with a lymphocyte count above 80% confer a better outcome and support the diagnosis of primary fetal hydrothorax . By definition, primary fetal hydrothorax is a diagnosis of exclusion once causes for secondary hydrothorax are ruled out (eg, genetic conditions, immune hydrops, thoracic masses, and infection) and preliminary evaluation of fetal hydrothorax include the ruling out such potential causes …”
Section: Introductionmentioning
confidence: 99%
“…2 By definition, primary fetal hydrothorax is a diagnosis of exclusion once causes for secondary hydrothorax are ruled out (eg, genetic conditions, immune hydrops, thoracic masses, and infection) and preliminary evaluation of fetal hydrothorax include the ruling out such potential causes. [3][4][5][6][7][8][9] One of the underlying etiologies that may significantly affect the long-term prognosis is genetic abnormality that is classified as chromosomal (aneuploidy and microdeletion/duplication) or single gene disorders. 10,11 Previous studies have reported a prevalence of 4.5% to 41% for karyotype abnormalities in pregnancies affected by pleural effusion.…”
Section: Introductionmentioning
confidence: 99%
“…W konsekwencji przedostawanie się płynów i białka do tkanek skutkuje uogólnionym obrzękiem płodu, który stanowi zagrożenie życia płodu, zwłaszcza jeśli pojawi się przed 24. tygodniem ciąży. Jednak wrodzony chłonkotok opłucnowy jest rzadką przyczyną uogólnionego obrzęku płodu o podłożu nieimmunologicznym -stanowi ok 5% przypadków [11,12,13].…”
Section: Rozwój Układu Chłonnegounclassified
“…Diagnostyka i rozpoznanie wrodzonego chłonkotoku opłucnowego powinno być rozszerzone o badania dodatkowe umożliwiające potwierdzenie bądź wykluczenie obecności w tkankach miękkich i trzewiach malformacji limfatycznych. Wrodzony chłonkotok ponadto obliguje lekarza do poszukiwania cech i objawów zespołów chorobowych, w których istotnym elementem są zaburzenia dotyczące układu chłonnego takich jak zespół Hennekama, zespół Aagenaesa, zespół obrzęk limfatyczny-podwójny rząd rzęs, zespół CLAPO, zespół ODELAID, zespół Turnera [2,11,12].…”
Section: Diagnostyka I Rozpoznanie Chłonkotokuunclassified
See 1 more Smart Citation